A Comprehensive Analysis of the Constitutional Framework and Judicial Interpretation of the Right to Privacy in India (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
At its core, privacy allows individuals to be undisturbed in their innermost selves. However, one’s interactions with society influence their autonomy, often challenging their freedom of choice. Both state and non-state institutions impact aspects of social life that affect personal freedom. Each of us have the implied right of privacy, which is considered a right in the common law to be let alone. The freedom in article 19 of the Indian Constitution include; freedom of speech and expression, freedom of assembly, freedom of association, freedom to questions and criticize the government, freedom to vote for the government one prefers. In India, the principle of personal liberty is governed by Article 21 of the Constitution that mandates that the right to life includes the right to privacy which the law must recognize and respect. This article forms the preamble of the Indian Constitution and gives the fundamental rights to life and personal liberty, which are inalienable rights that are not at the behest of the state. It comprises all dimensions that cover the aspect of meaningfulness of a person’s existence, protection of certain liberties to privacy, liberty, and the value of life. Much as dignity as part of right to life is concerned, it is viewed as one of the primary rights every deserving human ought to enjoy. Thus, the right to privacy encompasses negative or rights -based aspect as well as positive or interest-based element. On the negative side though, it protects people from unwarranted interference in their lives by the state and private parties regarding aspects of their lives like their sex lives, their religion, their political opinions, among others. It has been labelled the positive right as a thesis that requires states to eliminate hindrances to the formation of personal peculiarities.